1H Time Domain NMR to probe microstructural and mobility changes in Polyamide 11 exposed to H2S scavengers. What type of information can be assessed?. (August 2022) - Perez, Martha Gonzales; Lima, Aline Pinde; Moraes, Tiago Bueno; Chaves, Erica Gervasoni; Ruiz, Naira Machado da Silva; dos Santos Teixeira, Sylvia Correa; Honorato, Hercílio de Angeli; de Menezes, Sonia Maria Cabral; deAzevedo, Eduardo Ribeiro
Highlights: H2 S ethoxylated scavenger induces motional hindrance in the amorphous phase of PA11. Time domain NMR methods are effective for detecting the effect of H2 S ethoxylated scavenger in the microstructure of PA11. Permanent crosslinks among PA11 results from the exposure to ethoxylated scavengers. ABSTRACT: In this article 1 H Time Domain Nuclear Magnetic Resonance (TD-NMR) techniques were used to evaluate changes in the microstructure and chain mobility of polyamide 11 (PA11) induced by the exposure to a commercial H2 S scavenger. Dipolar based NMR pulse sequences such as 1 H mixed Magic Sandwich Echo (mixed-MSE), 1 H Dipolar Filtered Magic Sandwich Echo (DF-MSE) and 1 H Double Quantum time domain NMR (DQ-TDNMR), were applied. These methods provided information about changes in the segmental mobility, phase composition and chain crosslinking and entanglement in PA11. Mixed-MSE and DF-MSE results indicated that the contact with the H2 S scavenger does not substantially change the crystallinity of PA11, but induces significant decrease on the chain mobility of its amorphous phase. DQ-TDNMR results obtained in the melt state of PA11 suggest that such decrease occurs due to the formation of crosslinks between PA11 chains induced by the H2 S scavenger. In summary, while a simple mixed-MSE experiment may provide clear evidences about the polymer molecular integrity, more sophisticated methods such DF-MSE and DQ-TDNMR can be used to shed light on the nature of the degradation process. Because PA11 is one of the prime polymers used as barrier layer on flexible oil production pipelines, our results may be important for understating the set of conditions and parameters that contribute to its integrity